Elementary School Counsellors’ Perceptions Of Their Current And Ideal Role With Parents And Families - Samis, Kym; Allan, John; Echols, Frank (Canadian Journal of Counselling and Psychotherapy, 1993)
This study sought to identify B.C. elementary school counsellor's perceptions of (a) their "current" interventions with families, (b) their "ideal" forms of family interventions and (c) barriers to working with families. A survey instrument was mailed to 327 elementary counsellors and returned by 249 (76.2%). To determine if the differences between "current" and "ideal" means were significant, two-tailed paired samples Wests were conducted. The results indicated that counsellors prefer to work with children individually (M = 1.37), consult with teachers (M = 1.50), more than doing parent consultation (M=1.86). Parent education, parent consultation and family consultation were reported as appropriate services offered by school districts. "Work Load" and "Work Schedule" were found to be the largest barriers to performing more family interventions.